ADAPT: an algorithm incorporating PRO-C3 accurately identifies patients with NAFLD and advanced fibrosis - Daniels, Samuel J.; Leeming, Diana J.; Eslam, Mohammed; Hashem, Ahmed M; Nielsen, Mette J.; Krag, Aleksander; Karsdal, Morten A.; Grove, Jane I.; Guha, Indra Neil; Kawaguchi, Takumi; Torimura, Takuji; McLeod, Duncan; et al. (Wiley, 2018)
Background and Aim: Given the high global prevalence of non-alcoholic fatty liver disease (NAFLD), the need for relevant non-invasive biomarkers and algorithms to accurately stage disease severity is a critical unmet medical need. Identifying those with advanced fibrosis (≥F3) is the most crucial, as these individuals have the greatest risk of adverse, long-term, liver-related outcomes. We aimed to investigate the role of PRO-C3 (a marker of type III collagen formation) as a biomarker for advanced fibrosis in NAFLD. Methods: We measured PRO-C3 by enzyme-linked immunosorbent assay (ELISA) in two large independent cohorts with extensive clinical phenotyping and liver biopsy; 150 in the derivation and 281 in the validation cohort. A PRO-C3 based fibrosis algorithm that included Age, presence of DiAbetes, PRO-C3 (a marker of type III collagen formation), and plaTelet count (“ADAPT”) was developed. Results: PRO-C3 increased with fibrosis stage (rho 0.50 p<0.0001) and was independently associated with advanced fibrosis (OR=1.05, 95% CI 1.02-1.08, p= 0.003). ADAPT showed areas under the receiver operating characteristics curve (AUROC) of 0.86 (95% CI 0.79 to 0.91) in the derivation and 0.87 in the validation cohort (95% CI 0.83 to 0.91) for advanced fibrosis. This was superior to the existing fibrosis scores, aspartate aminotransferase (AST) to platelet ratio index (APRI), FIB-4 and NAFLD fibrosis score (NFS) in most comparisons. Conclusion: PRO-C3 is an independent predictor of fibrosis stage in NAFLD. A PRO-C3 based score (ADAPT) accurately identifies patients with NAFLD and advanced fibrosis and is superior to APRI, FIB-4 and NFS.